Navigating Customary Conflict: Adaptive Educational Governance for Sustainable Schooling - Cliford Racelino Ratulangi; Gabriela Karen Tuuk (Al-Qalam Institue, 2026)
This study aims to examine the impacts of customary conflicts on school continuity and identify adaptive educational governance strategies that support educational sustainability in conflict-affected indigenous communities. A qualitative case study approach was employed using semi-structured interviews, observations, and document analysis involving school principals, teachers, customary leaders, parents, and education officials. The data were analyzed thematically to identify patterns of educational disruption and adaptive governance practices. The findings reveal that customary conflicts disrupt educational continuity through temporary school closures, reduced teacher and student attendance, interruptions to learning activities, and limited access to educational services. In response, schools implement adaptive governance strategies through collaboration with customary leaders, community engagement, flexible academic arrangements, and crisis-response mechanisms. These strategies demonstrate the importance of locally grounded governance in maintaining educational services during conflict. The study proposes an Adaptive Educational Governance Model Based on Local Wisdom that emphasizes collaboration among schools, communities, customary institutions, and government agencies. This model provides a framework for strengthening educational resilience, maintaining school continuity, and developing context-sensitive educational policies for indigenous and conflict-affected communities.